THE INFLUENCE OF WAQF LITERACY, RELIGIOSITY, AND TRUST IN WAQF MANAGEMENT INSTITUTIONS ON WAQF DECISIONS - Triyatno, Ghazy; Ikhwan, Ari Afiful; Ekowati, Vivin Maharani; Supriyanto, Achmad Sani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study examines the impact of Islamic financial literacy, religiosity, and trust in waqf institutions on waqif decisions to endow funds. Using decision theory, this study uses quantitative methods with the Partial Least Squares-Structural Equation Model (PLS-SEM) approach. This study involved 182 graduate students of the State Islamic University of Malang as respondents. Data were collected through an online questionnaire and analyzed using SmartPLS software. The results showed that Islamic financial literacy significantly positively affects waqf decisions, emphasizing the role of understanding in encouraging waqf contributions. Religiosity also positively affects waqf decisions, reflecting the importance of spiritual motivation. In addition, trust in waqf institutions plays the most dominant role, where transparency and accountability increase public trust and encourage participation. The findings highlight the need for strategic efforts to improve waqf literacy, strengthen religiosity, and build trust to optimize waqf potential. This research provides input to waqf regulators and nazirs to continuously improve literacy and education on waqf as well as transparency of managed waqf funds, to increase public trust in waqf institutions.